2011
DOI: 10.5483/bmbrep.2011.44.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine derived from Staphylococcus aureus-engulfed macrophages functions as a potent stimulant for the induction of inflammatory cytokines in mast cells

Abstract: In this study, we attempted to isolate novel mast cell-stimulating molecules from Staphylococcus aureus. Water-soluble extract of S. aureus cell lysate strongly induced human interleukin-8 in human mast cell line-1 and mouse interleukin-6 in mouse bone marrow-derived mast cells. The active molecule was purified to homogeneity through a C18 reverse phase HPLC column. By determination of its structure by MALDI-TOF and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…It has been shown that mast cells produce certain cytokines, e.g. TNF‐ α and IL‐6, in response to S. aureus . Here we extend these findings by unbiased technology and show that peritoneal mast cells also up‐regulate a number of additional pro‐inflammatory compounds when encountering S. aureus , including IL‐3, IL‐13, Oncostatin M, Lif, and chemokines Ccl3, Ccl7 and Cxcl2.…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that mast cells produce certain cytokines, e.g. TNF‐ α and IL‐6, in response to S. aureus . Here we extend these findings by unbiased technology and show that peritoneal mast cells also up‐regulate a number of additional pro‐inflammatory compounds when encountering S. aureus , including IL‐3, IL‐13, Oncostatin M, Lif, and chemokines Ccl3, Ccl7 and Cxcl2.…”
Section: Discussionsupporting
confidence: 75%
“…One factor produced in response to microbial infection that prevents airway hyperresponsiveness is adenosine. Moreover, bacteria or macrophages that have engulfed bacteria were found to release adenosine, which influenced cytokine release from mast cells (33). We speculate that adenosine produced by bacteria or by macrophages engulfing bacteria also influences allergen sensitization by effects on APCs.…”
Section: Myeloid Cells As Targets Ofmentioning
confidence: 94%
“…Mouse bone marrow stem cell-derived mast cells (mBMMCs) were prepared and cultured as previously described (29,30). Briefly, mouse bone marrow stem cells were isolated from the femur and tibia of 6∼8-week-old mice, and cultured to a final density of 1 × 10 6 cells/ml in Iscove’s modified Dulbecco’s medium (IMDM) (Gibco) supplemented with L-glutamine (2 mM, Sigma), heat inactivated fetal calf serum (10%, Gibco), penicillin (100 IU/ml, Sigma), streptomycin (100 μg/ml, Sigma), murine stem cell factor (SCF) (30 ng/ml, Peprotech), and IL-3 (30 ng/ml, Peprotech) at 37℃, in 5% (v/v) CO 2 air with 95% humidity.…”
Section: Methodsmentioning
confidence: 99%